Indonesian Cultural Values as Pillars of Academic Resilience: A Study on Indonesian Higher Education Students - Kaloeti, Dian Veronika Sakti; Kurnia S, Ayu; Swandi, Ni Luh Indah Desira; Lufityanto, Galang; Indrawati, Nur Diana (Universitas Pendidikan Ganesha, 2024)
This study identifies the challenges faced by students in higher education, which require academic resilience to overcome effectively. The study aims to analyze the role of local Indonesian values, such as